FACTORS AFFECTING BEHAVIORAL INTENTION IN USING GO-PAY WITH THE MODIFIED UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY 2 MODEL (UTAUT2) - Nuriska, Alfia; Asakdiyah, Salamatun; Setyawan, Rai Raka (Muhammadiyah International Journal of Economics and Business, 2018)
The   development   of   payment   systems  in   Indonesia   is  in   line   with   the  global   technological advancements and followed by new innovations, including the presence of e-money.As a subsidiary of  PT Aplikasi  Karya Anak  Bangsa  (Go-Jek),  PT  Dompet Anak  Bangsa  is the holder  of  the  Go- Pay  e-money license and  included  as one of  32  companies  that have obtained  license as  e-money operators from Bank Indonesia. Despite the current high transaction growth of Go-Pay, it may not survive without any efforts to improve its service quality and expand the consumer preferences in using  Go-Pay. Therefore,  it  is necessary to  identify  the factors that  influence behavioral  intention in  using  Go-Pay. This  study  aims to  examine  and determine the factors  that influence  behavioral intention in using Go-Pay with the modified Unified Theory of Acceptance and Use of Technology2  Model  (UTAUT 2).  This  study  uses a quantitative  method  with  a  questionnaire  as the research instrument. The population of this study is Go-Pay users in the Special Region of Yogyakarta. The method  of  data analysis is SEM-PLS.   The  results showed  that there were  three  factors that were significant in influencing people?s interest in using Go-Pay, namely: Habit, Facilitating Condition, and Price Value.